Using Concurrent PC DOS - Dahmke, Mark. (New York : McGraw Hill Education, 1986)
The primary advantage of concurrency and windows on a single-user system is that instead of having just one console and the ability to run just one program at a time, the user may execute several applications at once.
Chapter 1. Introduction -- Chapter 2. Concurrent PC DOS compatibility -- Chapter 3. The concept of concurrency -- Chapter 4. Windows in concurrent PC DOS -- Chapter 5. Diskettes and fixed disks -- Chapter 6. The file manager -- Chapter 7. Creating and modifying menus -- Chapter 8. The printer managers -- Chapter 9. The backup/restore facility -- Chapter 10. Customizing your personal computer.
Includes bibliographical references and index.
Keywords: CONCURRENT PC DOS (COMPUTER OPERATION SYSTEM)